Naram-Suen and the Mus huššu serpents - Frayne, Douglas (JAOS, 1982)
A text in literary Old Babylonian in the British Museum published by W. G. Lambert was thought by the editor to deal with king Naram-Suen of Akkad. The text seems to deal rather with events commemorated in a year formula of Naram-Suen of Ešnunna, namely the king's affixing of a pair of metal serpents on a gate.